OPTIMIZATION ILS IN LKVO VODOCHODY (Perner's Contacts, 2010)
The article focuses on sharp skidding equipment in LKVO Vodochody airport. Part of the article is dedicated to general overview about system ILS configuration. Possibilities of most effective and quick current navigation system ILS in LKVO Vodochody optimization are metioned in the following part of the article. There is also included detailed analysis of the current statement related to separate navigation skidding equipments.
Keywords: air traffic; navigation; frequence; beacon